HEALTH CREATOR: ANATOMY OF A FUZZY CONCEPT - Vicari, Stefania; Ditchfirld, Hannah; Guo, Yumeng; Morena, Nina; Dimya Htite, Elly; Ahisar, Yitzchok; Hayman, Victoria; Rentschler, Carrie A; Meguerditchian, Ari N; Holroyd, Deanna; Baker, Stephanie Alice; Tiidenberg, Katrin Tiidenberg; et al. (AoIR Selected Papers of Internet Research, 2026)
“Health creator” is now a common term across academic work (e.g., Avella, 2024) and public parlance (e.g., Moore, 2020), also featuring in the title of one of the traditional panels at AoIR2024. However, as a label, it directs our attention away from matters of ill health (e.g., suffering, diagnosis, loss), overlooking the work of those who share their lived experience of illness and missing the multiple implications this work has for creators, audiences and wider publics. As a concept, it remains underdeveloped– even despite the growing body of both academic research on platform economies and creator cultures (e.g., Cunningham and Craig, 2021) and global policy interested in the influence of social media on lay and public understandings of health and medicine (e.g., WHO, 2025).The panel aims to shed light on the wider spectrum of creator work that draws on matters of health, illness and care and develop a conceptual toolkit to interpret this work, understand its labour and explore its implications. It reviews evidence of lived experience, epistemic work, credibility, and influence through five case studies approaching creators and their content on and through Facebook, Instagram, X, TikTok, YouTube, BlueSky and LinkedIn. To provide a comprehensive account of the processes through which content is created, shared, and audienced, the panel explores all sites of meaning making: it starts by focusing on creators themselves (paper 1), to then draw attention to content (paper 2 and 3), platform structures (paper 4), and audiences (paper 5).